Crystal structure of a membrane-bound O-acyltransferase. (11th October 2018) - Ma, Dan; Wang, Zhizhi; Merrikh, Christopher; Lang, Kevin; Lu, Peilong; Li, Xin; Merrikh, Houra; Rao, Zihe; Xu, Wenqing
Abstract Membrane-boundO -acyltransferases (MBOATs) are a superfamily of integral transmembrane enzymes that are found in all kingdoms of life1 . In bacteria, MBOATs modify protective cell-surface polymers. In vertebrates, some MBOAT enzymes—such as acyl-coenzyme A:cholesterol acyltransferase and diacylglycerol acyltransferase 1—are responsible for lipid biosynthesis or phospholipid remodelling2, 3 . Other MBOATs, including porcupine, hedgehog acyltransferase and ghrelin acyltransferase, catalyse essential lipid modifications of secreted proteins such as Wnt, hedgehog and ghrelin, respectively4–10 . Although many MBOAT proteins are important drug targets, little is known about their molecular architecture and functional mechanisms. Here we present crystal structures of DltB, an MBOAT responsible for thed -alanylation of cell-wall teichoic acid in Gram-positive bacteria11–16, both alone and in complex with thed -alanyl donor protein DltC. DltB contains a ring of 11 peripheral transmembrane helices, which shield a highly conserved extracellular structural funnel extending into the middle of the lipid bilayer. The conserved catalytic histidine residue is located at the bottom of this funnel and is connected to the intracellular DltC through a narrow tunnel. Mutation of either the catalytic histidine or the DltC-binding site of DltB abolishes thed -alanylation of lipoteichoic acid and sensitizes the Gram-positive bacteriumBacillus subtilis to cell-wall stress, which suggests cross-membrane catalysis involving the tunnel. Structure-guided sequence comparison among DltB and vertebrate MBOATs reveals a conserved structural core and suggests that MBOATs from different organisms have similar catalytic mechanisms. Our structures provide a template for understanding structure–function relationships in MBOATs and for developing therapeutic MBOAT inhibitors. Crystal structures of DltB, a bacterial membrane-boundO -acyltransferase, are reported both alone and in complex with thed -alanyl donor protein DltC.